Everything you need to ace American history in one big fat notebook : the complete middle school study guide - Rothman, Lily; Bigler, Philip; Hall, Tim (New York : Workman Publishing, 2016)
A workbook that examines American history on a middle school level. Organized by key concepts, the text includes mnemonic devices, definitions, timelines and doodles to help the subject stick in your brain, so you can ace your class.
Prehistory--Early 1600s -- Colonial America, 1607-1780s -- American Revolution and the early Republic, 1776-1791 -- American expansion, 1801-1861 -- Civil War and Reconstruction, 1850s-1870s -- Reshaping the nation, 1850-1917 -- World wars and modern America, 1900s-1930s -- World War II, 1930s-1945 -- Post-World War II era, 1945-1980 -- American history... and current-ish events!
"From the brains behind Brain Quest!"--Front cover.
English language and literature.
Keywords: Readers for new literates; Study Guides; United States -- History -- Study and teaching (Middle school) -- Juvenile literature; United States -- History -- Study and teaching (Middle school); United States -- History -- Study and teaching (Middle school.); Study guides